Fe TABLET WITH SWEET ORANGE (Citrus x sinensis) JUICE SUBSTITUTION EFFECTS HEMOGLOBIN LEVEL IN TRIMESTER III PREGNANT WOMEN WITH ANEMIA - Umu Qonitun; Miftahul Munir; Irma Fitria; Pebpy Eko Handayani (UNIVERSITAS AIRLANGGA, 2023)
Background: Organic acids such as ascorbic acid (vitamin C) can help absorb iron by reducing Ferry to Fero which is easily absorbed 3-6 times (Almatsier, 2014). The purpose of this study is whether Fe tablets with the addition of sweet orange juice (citrus x sinesis) can affect hemoglobin levels in third trimester pregnant women with anemia. Method: The study design was a pre-post control group design. The population in this study were all 35 pregnant women with anemia in the third trimester, using a simple random sampling technique. The sample size is 32 respondents with each group consisting of 16 respondents. The treatment group was given Fe tablets & sweet orange juice for 14 days. Result: Most of the hemoglobin levels of anemic pregnant women in the third trimester before being given Fe tablets experienced moderate anemia by 9 (56.3%) and after being given Fe tablets experienced an increase to mild anemia by 9 respondents (56.3%). There is an effect of giving Fe tablets with sweet orange juice (citrus x sinensis) on increasing hemoglobin levels in third trimester anemic pregnant women. Conclusion: Giving Fe tablets with sweet orange juice (citrus x sinensis) has a more significant role in increasing hemoglobin levels in anemic pregnant women in the third trimester, as health workers it is recommended to do more education to the public, especially pregnant women about how to consume Fe tablets with sweet orange juice (citrus x sinensis) so that absorption of Fe is better